2019
DOI: 10.3390/medsci7030041
|View full text |Cite
|
Sign up to set email alerts
|

Dually Efficacious Medicine Against Fibrosis and Cancer

Abstract: Although there is a contemporary consensus of managing a severe disease with multi-targeted approach-based therapeutic combinations, it should not be ignored that certain patho-biological pathways are shared by distinct medical conditions and can be exploited to develop an exceptional type of medication conferring a dual efficacy. This article thus presents a spectrum of emerging molecular targets that substantially contribute to the pathogenesis of both fibrotic and neoplastic disorders, including kinase acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…However, other studies have suggested that weight loss may not reverse epigenetic changes induced in obese adipose tissue [ 71 ], and the impact of weight loss on the function of lung stromal cells needs to be investigated. Given the similarities that we observed among lung stromal cells in obesity- and cancer-associated fibroblasts, therapeutics in development to target inflammatory characteristics of fibroblasts as well as antifibrotic agents may also have efficacy to limit metastasis in obese breast cancer patients [ 72 , 73 ]. Further studies are necessary to determine how obesity alters stromal cells in the microenvironment of other frequent sites of breast cancer metastases, such as liver and bone.…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies have suggested that weight loss may not reverse epigenetic changes induced in obese adipose tissue [ 71 ], and the impact of weight loss on the function of lung stromal cells needs to be investigated. Given the similarities that we observed among lung stromal cells in obesity- and cancer-associated fibroblasts, therapeutics in development to target inflammatory characteristics of fibroblasts as well as antifibrotic agents may also have efficacy to limit metastasis in obese breast cancer patients [ 72 , 73 ]. Further studies are necessary to determine how obesity alters stromal cells in the microenvironment of other frequent sites of breast cancer metastases, such as liver and bone.…”
Section: Discussionmentioning
confidence: 99%
“…1A, IC 50 $130-220 nmol/L; Ki $15 against human ATX), succeeded in halting the progression of idiopathic pulmonary fibrosis in phase IIa clinical trials (31,32), and it is now being tested in a phase III trial (33). Significantly, many therapeutics that are effective against fibrosis are also used to improve cancer treatments (34). It was, therefore, important to establish if an ATX inhibitor that is in clinical trials for fibrosis has positive effects on the treatment of cancers.…”
Section: Introductionmentioning
confidence: 99%
“…However, other studies have suggested that weight loss may not reverse epigenetic changes induced in obese adipose tissue (Rossi et al, 2016), and the impact of weight loss on the function of lung stromal cells needs to be investigated. Given the similarities that we observed among lung stromal cells in obesity and cancer-associated fibroblasts, therapeutics in development to target inflammatory characteristics of fibroblasts as well as anti-fibrotic agents may also have efficacy to limit metastasis in obese breast cancer patients (Chen, 2019;Liu et al, 2019). Further studies are necessary to determine how obesity alters other frequent sites of breast cancer metastases.…”
Section: Discussionmentioning
confidence: 89%